Analysis of the Difficulties Faced by Seventh Grade Students of Mts Al-Haq Margahayu in Mastering Listening (Maharah Istima’) and Speaking Skills (Maharah Kalam) in Arabic Language Learning: English - Marlina, Lina; khairunnisa Hasugian (Tatsqifiy: Jurnal Pendidikan Bahasa Arab, 2025)
The focus of this study was to evaluate the problems faced by the seventh grade students of MTs Al-Haq Margahayu in mastering the skills in Arabic language learning, ( maharah istima ) listening and ( maharah kalam ) speaking. Data were collected through direct observation and survey using a qualitative descriptive case study approach. The findings of this study showed students’ difficulties such as limited vocabulary, accent variations, low self-confidence and lack of speaking practice were also the main challenges. The use of the book "Al-Mumtaz fi Al- Hiwarat Al- Yaumiyah " from BISA institute helps to improve students’ ability in speaking, although challenges such as vocabulary limitations and accent understanding still have to be overcome. This study suggests the need for more interactive and diverse learning approaches to improve students’ Arabic language skills.